Analysis of genome size of Aquilaria species and characterization of terpene synthase transcripts of Aquilaria malaccensis Lam. - Azman, Farah Hanani (2018)
Aquilaria species (Thymelaeaceae family) are an important botanical resources for the fragrant agarwood. Agarwood is mainly composed of terpenoids that are produced by a family of enzyme called terpene synthases (TPS). The species have been studied for the decades, however, the size of its genome which are important for breeding effort is yet to be analyzed. In addition, identification of terpenoid biosynthesis gene in Aquilaria spp. is critical for a deeper understanding of the mechanisms involved in agarwood formation. In this study, the genome size of five Aquilaria species which include A. hirta, A. malaccensis, A. subintegra, A. sinensis, and A. microcarpa. were estimated by using flow cytometry. The results showed no large variation in the 2C- values of the five species (1.35 to 2.23 pg). The TPS genes was analyzed in one the five species, A. malaccensis based on the previously developed in-house transriptome database. Putative TPS transcripts in A. malaccensis encoding monoterpene, sesquiterpene and diterpene were found clustered within known TPS families. A transcript encoding linalool synthase, an acyclic monoterpene common to floral scents of numerous plant was selected for protein expression analysis in E. coli where the protein accumulated in insoluble form. Collectively, the information obtained on the 2C-values can help elucidate the underlying mechanism in the evolutionary forces driving genome size variation in Aquilaria species while identification of putative TPS transcripts in A. malaccensis provides a clue for the role of TPS in agarwood formation in that particular species.